2013
DOI: 10.1155/2013/861496
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Tissue Visfatin/Nicotinamide, Phosphoribosyltransferase (Nampt), Retinol Binding Protein-4, and Vaspin Concentrations and Insulin Resistance in Morbidly Obese Subjects

Abstract: Visfatin/Nampt, vaspin, and retinol binding protein-4 (RBP-4) play an important role in insulin resistance. The objectives of this study were to measure visfatin/Nampt, vaspin, and RBP-4 concentrations in blood, liver, muscle, subcutaneous, omental, and mesenteric adipose tissues in morbidly obese subjects and investigate their relationship to insulin resistance. Blood and tissue samples were collected from 38 morbidly obese subjects during Roux-en-Y surgery. Insulin resistance biomarkers were measured using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…Vaspin expression has been found in human adipose tissue as well as stomach, liver, pancreas, placenta and muscle tissue . While the specific tissues secreting the most vaspin remain unknown, Mm et al .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Vaspin expression has been found in human adipose tissue as well as stomach, liver, pancreas, placenta and muscle tissue . While the specific tissues secreting the most vaspin remain unknown, Mm et al .…”
Section: Discussionsupporting
confidence: 60%
“…The added adipogenesis of SAT, with improved IR, is likely associated with an upregulation in vaspin gene expression in SAT . Goktas et al . also found the expressions of vaspin in SAT, VAT and rectus abdominis muscle were different in obese subjects in both normal, prediabetic and diabetic groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, vaspin mRNA level was higher in OLETF rats than in non-diabetic control rats [1]. Further, vaspin expression was observed in humans [4,5] or mice [6] in several tissues such as adipose tissue, liver, skeletal muscle, pancreas, and skin, with the highest production being observed in the liver or skin.…”
Section: Visceral Adipose Tissue-derived Serine Protease Inhibitor (Vmentioning
confidence: 90%
“…Such conflicting data may be attributed to the difference in the specificity of the immunoassays used in the different studies [24]. Moreover, Goktas et al [25] (2013) concluded that correlations of visfatin with insulin resistance markers are tissue dependent.…”
Section: Discussionmentioning
confidence: 99%